IgA nephropathy in hereditary angioedema. Issue 808 (February 1993) - Srinivasan, J.; Beck, P.
Abstract : Hereditary angioedema is an autosomal dominant disorder of the complement system in which there is a deficiency of the inhibitor of the activated first component of complement. We have previously reported on three generations of a family with classic hereditary angioedema. Three members of this family have now developed IgA nephropathy. The association of hereditary angioedema with various immunoregulatory disorders has been previously reported but this is the first report of IgA nephropathy in association with this condition.